BEM-ESTAR SUBJETIVO E AUTOEFICÁCIA EM DEPENDENTES DE COCAÍNA/CRACK - Ferreira, Eliane Cardoso (2013)
This study aimed to identify and describe associations between subjective well-being, construct formed by general satisfaction with life and positive and negative affects, and self-efficacy for drug abstinence in cocaine/crack in the process of withdrawal. Used to assess the variables, the Scales of Positive and Negative Affects, General Satisfaction with Life, Self-efficacy for Withdrawal of Drug Evaluation for Change, University of Rhode Island and a questionnaire on socio-demographic and socio-cultural. 70 men participated, cocaine/crack, young and low education. They were people of incomes of up to three minimum wages (63%) who were hospitalized more than once (65%), self-reported abstinence at the time of data collection. Participants had average levels of self-efficacy for abstinence from drugs, low levels of subjective well-being, and were satisfied with their lives. Calculations of Pearson correlation revealed no association between subjective well-being and self-efficacy for abstinence from drugs, including readiness to change drug use and subjective well-being, nor between readiness to change drug use and self-efficacy for abstinence drugs. Results of analysis of variance revealed no differences in the levels of subjective well-being among different groups of readiness for change nor between the mean self-efficacy for abstinence from drugs among different groupings of readiness for change in drug use. The discussion touched on the results of the fact that the admission of participants was voluntary or involuntary, length of stay, their stage of readiness to change their behavior of drug and the characteristics of their group withdrawal on the literature of the area. Finally, he pointed out, in conclusion, limitations and future research agenda.